High Wave Activity Observed in Patagonia, Southern America: Generation by a Cyclone Passage over Andes Mountain Range - Pulido, Manuel Arturo (2013)
The Antarctic peninsula and Patagonia region (South of South America) have recently been identified as one of the regions with the highest gravity wave activity in the world. In this work, the generation and propagation of gravity waves in the Patagonia region in an event of strong wave activity from 30 October 1995 to 1 November 1995 is examined by means of radiosonde measurements and simulations with the Weather Research and Forecasting (WRF) model. The waves are generated by strong surface winds found near the Andes mountains at a latitude of 49-51◦S. The strong low-level winds are related to an extratropical cyclone that propagates south-eastward in the South Pacific ocean and approaches the western coast of the continent. The waves propagate southeast toward Tierra del Fuego and they continue their propagation over the Drake Passage. They are found to propagate long meridional (lateral) distances due to the shear background conditions. This fact is corroborated with WRF simulations and a novel technique that combines wavelet analysis and backward ray tracing. Therefore, this work provides further evidence that high gravity wave activity found by several works over Drake Passage may have an orographic origin. During the orographic wave event which lasts about 72 hours, the horizontal wavelength is unexpectedly found to change day-to-day. The analysis shows that changes in the near-surface meteorological conditions produced by the cyclone passage may trigger different components of the forcing orography. The orographic waves propagate toward their critical levels which are found at 25 km and above. The radiosonde measurements show that the wave is breaking continuously along a wide altitude range, this finding from measurements supports the picture of a continuous wave erosion along the ray path instead of an abrupt wave breaking for the examined wave event.